(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
This paper takes an overview of African-American’s experiences in America. It is a fact that racism and slavery are the major issues in African-American literature. It is against this background, that this paper attempts to make readers realize the thematic pre-occupation in LeRoi Jones’s Dutchman by analyzing the concept of slavery and racial segregation in African-Americans. Also, it examines the historical perspective of African-American writing narrative, and the effects of racism and slavery, which include: loss of identity, oppression, assault, poverty, injustice, amongst others, and the ways in which the African-Americans reactes to racism. Therefore, we can say that African-American literature was and is still written to protest against ill-treatment, racial discrimination and injustice meted out to Blacks in all ramifications, with the vision of restoring their self pride, culture, and identity as portrayed in Dutchman. Racial scholars argue strongly that, racism brings rate of mortality, morbidity, and overall well-being that vary depending on socially assigned race. Eliminating racism and slavery is therefore central to achieving freedom. The paper adopts antiracism as a framework as well as a method for this study. The paper finds out that racism and slavery is inhuman, and concludes that, the fight against racism and slavery is worth dying for.